Analysis of Brain Lipids in the Early-Onset Tay–Sachs Disease Mouse Model With the Combined Deficiency of β-Hexosaminidase A and Neuraminidase 3 - Can, Melike; Sengül, Tugce; Demir, Secil Akyildiz; İnci, Orhan K.; Basırlı, Hande; Seyrantepe, Volkan (Frontiers in Molecular Biosciences, 2022)
Introduction: Tay-Sachs disease is an autosomal recessively inherited lysosomal storage disease that results from loss-of-function mutations in HEXA gene coding -hexosaminidase A. HEXA gene deficiency affects the central nervous system owing to GM2 ganglioside accumulation in lysosomes resulting in progressive neurodegeneration in patients. We recently generated a novel mice model with the combined deficiency of β-Hexosaminidase A and Neuraminidase 3 (Hexa-/-Neu3-/-) which mimics both the neuropathological and clinical abnormalities of early-onset Tay-Sachs disease. Here, we aimed to explore the secondary accumulation of lipids in the brain of Hexa-/-Neu3-/- mice. Materials and methods: In the cortex and hippocampus of 5-month-old of WT, Hexa-/-, Neu3-/-, and Hexa-/-Neu3-/- mice lipid levels belonging to glycerolipids, glycerophospholipids, and sterol lipids were evaluated using shotgun lipidomics approach. The levels of myelin were also assessed by Luxol Fast Blue staining and immunohistochemistry using antibodies against myelin basic protein. We further examined glycoconjugate and cholesterol levels by Periodic Acid-Schiff and Filipin staining, respectively. Toluidine Blue staining was also performed to display axonal degeneration. Results: Among glycerophospholipids, we demonstrated elevated levels of phosphatidylcholine-ether and lysophosphatidylcholine while decreased levels of phosphatidylcholine and phosphatidylserine in both cortex and hippocampus of Hexa-/-Neu3-/- mice. In the glycerolipid class, we showed an alleviated level of sphingomyelin in both cortex and hippocampus, but the higher levels of diacylglycerol and triacylglycerol were detected in only the hippocampus of Hexa-/-Neu3-/- mice. The lower level of sterol was also detected in the cortex of Hexa-/-Neu3-/- mice, but not in the hippocampus. Histochemical studies showed a decrease in myelin level and axonal degeneration indicating neuronal pathology in the brain of Hexa-/-Neu3-/- mice. Although glycoconjugate accumulation was evident both in the cortex and hippocampus, we did not detect any changes in the level of cholesterol Conclusion: Our results indicate that alterations in lipid metabolism and neuropathology, such as demyelination and axonal degeneration might be related to the dysfunctionality of lipid-related cellular pathways like autophagy. Understanding of brain-specific lipid alterations contributes to evaluating the effectiveness of treatments in Hexa-/-Neu3-/- mouse in future studies.